An efficient algorithm for detecting traffic congestion and a framework for smart traffic control system - Karim, Dewan Tanzim ul; Shahid, Nafis Ibn; Mamun, Abdullah Al; Islam, Md. Rokebul (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.